2015
DOI: 10.1590/01000683rbcs20150194
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical Properties and Growth of Sunflower (Helianthus Annuus L.) as Affected by the Application of Organic Fertilizers and Inoculation With Arbuscular Mycorrhizal Fungi

Abstract: The use of organic fertilizers and the inoculation of mycorrhizal fungi in the cultivation of oil crops is essential to reduce production costs and minimize negative impacts on natural resources. A field experiment was conducted in an Argissolo Amarelo (Ultisol) with the aim of evaluating the effects of fertilizer application and inoculation of arbuscular mycorrhizal fungi on the growth attributes of sunflower (Helianthus annuus L.) and on soil chemical properties. The experiment was conducted at the Federal U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The screen factor was not significant; in other words, root contact in the competitive process did not alter the percentage of mycorrhizal colonization of soybean. Mycorrhizal symbiosis strongly influences the patterns and intensity of effects of intra and interspecific competition between weed, and the benefit degree of the species is consequence of the plant mycorrhizal dependence (Rinaudo, Bárberi, Giovannetti, & Van Der Heijden, 2010;Silva et al, 2015). As observed, other species involved in the competition process also presented influences of mycorrhizal associations.…”
Section: Resultsmentioning
confidence: 60%
“…The screen factor was not significant; in other words, root contact in the competitive process did not alter the percentage of mycorrhizal colonization of soybean. Mycorrhizal symbiosis strongly influences the patterns and intensity of effects of intra and interspecific competition between weed, and the benefit degree of the species is consequence of the plant mycorrhizal dependence (Rinaudo, Bárberi, Giovannetti, & Van Der Heijden, 2010;Silva et al, 2015). As observed, other species involved in the competition process also presented influences of mycorrhizal associations.…”
Section: Resultsmentioning
confidence: 60%
“…However, AMF species could influence protein content differently. Silva et al [39] found that crude protein levels in seeds were not significantly affected by inoculation of sunflower with Glomus fasciculatum. On contrary, protein content was enhanced in seeds of soya inoculated with Glomus mosseae [40], maize inoculated with AMF mixture (Glomus intraradices, Glomus aggregatum, Glomus viscosum, Glomus etunicatum, and Glomus claroideum) [41], and wheat inoculated with G. intraradices and G. mosseae [30].…”
Section: Resultsmentioning
confidence: 99%
“…Mycorrhizal fungi induce plant growth through increasing the availability of mineral nutrients such as P, Zn and Cu (Phiri et al, 2003). Inoculation of roots with AMF can also reduce the harmful effects of chemical fertilizer used in conventional farming (Silva et al, 2015), increase plant defense mechanisms to alleviate different stresses (Mayer et al, 2017) and aid in weed control (Veiga et al, 2011). In addition, colonization of arbuscular mycorrhiza (AM) in the rhizosphere enhances growth (Jalaluddin and Hamid, 2011;Silva et al, 2015) and morphological parameters (Kavitha and Nelson, 2014) in sunflower.…”
Section: Introductionmentioning
confidence: 99%
“…Inoculation of roots with AMF can also reduce the harmful effects of chemical fertilizer used in conventional farming (Silva et al, 2015), increase plant defense mechanisms to alleviate different stresses (Mayer et al, 2017) and aid in weed control (Veiga et al, 2011). In addition, colonization of arbuscular mycorrhiza (AM) in the rhizosphere enhances growth (Jalaluddin and Hamid, 2011;Silva et al, 2015) and morphological parameters (Kavitha and Nelson, 2014) in sunflower. AMF applications increased head diameter, seed number in head, seed and oil yield and oil percentage when compared with nontreatment (control) (Soleimanzadeh, 2010).…”
Section: Introductionmentioning
confidence: 99%